Status of Air Pollution over the Last Three Decades in Thimphu City, Bhutan - Sharma, Govinda Prasad; Sapkota, Ramesh Prasad; Mool, Enna; Gurung, Tulsi; Maskey Byanju, Rejina (Journal of Institute of Science and Technology, 2021)
With an increasing human population and vehicles, air pollution in Thimphu City is growing and causing a risk to human health, properties, and ecosystems. The population of Thimphu was 79,185 in 2005 but in 2017 it surged up to 114,551. An increase in the human population has also led to the rising demands for vehicles and thus increased the vehicular emissions in the area. Additionally, the use of traditional fuels, burning of waste and agriculture residues, forest fire, and transboundary pollutants are other sources resulting in poor air quality in Thimphu City. Air pollution data from journal articles, government documents, reports from national and international organizations, and books were reviewed. Concentrations of PM10, PM2.5, SO2, NO2 were increasing over the decades. The annual average PM10 recorded in Thimphu was 28 µg/m3 in 2005, 47 µg/m3 in 2010, 43 µg/m3 in 2014, and 42 µg/m3 in 2015. Winter months were found to have higher PM10 and PM2.5 concentrations. The 24-hourly average concentrations of SO2 ranged from 0.0 to 6.9 µg/m3 and NO2 8.2-26.6 µg/m3. There is a need for comprehensive studies to identify spatial and temporal variations in the ambient concentration of the pollutants in the area. Strict enforcement of the legal frameworks is essential for the mitigation of air pollution in Thimphu City.